Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

Additive-free modified electrospray for fabricating smooth and highly permselective polyamide reverse osmosis membranes - Muhammad Ali Hasnain; Muhammad Mujahid; Long-Fei Ren; Jiahui Shao (Journal of Environmental Chemical Engineering, 2026)

Partitioning of granular flows at valley bifurcation under varying control conditions - Hasnain Gardezi; Xingyue Li; Yu Huang; Syed Muhammad Mudassir Zia; Irtza Ali; Taimur Mazhar Sheikh (Engineering Geology, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Building Information Modelling (BIM) adoption in developing economies: an analysis of barriers, critical success factors, and a public infrastructure viability framework - Qaim Shah; Syed Saad; Muhammad Hasnain; Waseem Khan; Ijaz Ahmad; Abdul Haq (Innovative Infrastructure Solutions, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

Potential Application of Tamarind Seed Extract as Coagulant Aid in Alum-Based Removal of Polyamide Microplastics - Muhammad Adli Hanif; Naimah Ibrahim; Man Yung Ho; Masitah Hasan; Farrah Aini Dahalan; Nabilah Aminah Lutpi; Norzila Othman; Mohamed Hasnain Isa (International Journal of Environmental Research, 2026)

Fabrication of Magnetic Polyvinyl Alcohol and Polyvinyl Pyrrolidone Ferrite Nanocomposites for the Removal of Reactive Dyes from wastewater by Adsorption Process - Muhammad Hasnain; Abdul Qadir Ahmad; Muhammad Junaid; Anam Zulfiqar; Rizwan Ali; Hafiz Muhammad Waqar Abid; Rajesh Kumar Manavalan; Khalid Bilal; Mahmoud F. Y. Shalaby (Water, Air, & Soil Pollution, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Nafion-assisted n-TOPCon bottom cells integrated with FAPbI₃ perovskite top cells for high-efficiency four-terminal tandem solar cell under rear-albedo illumination - Alamgeer; Hyunseo Lee; Shurouq Abdulqadir Mohammed; Muhammad Quddamah Khokhar; Hasnain Yousuf; Sangheon Park; Jaeki Jeong; Junsin Yi (Chemical Engineering Journal, 2026)

Genetic programming-based closed-form solutions for predicting the compressive strength of cement-treated soils - Muhammad Hasnain Ayub Khan; Akbar A. Javadi; Adel Abdallah; Olivier Cuisinier (Transportation Geotechnics, 2026)

Retraction Note: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2026)

Optimisation of biomass-derived Propanol–Gasoline blends for sustainable bioenergy utilisation using response surface methodology - Muhammad Arslan Aslam; Ammar Hashmi; Muhammad Ashfaq; Muneeb-ur Rehman; Shah Nawaz Khan; Fakhar-ul Hasnain; Cheol Woo Park (Biomass and Bioenergy, 2026)

Computationally guided synthesis and biological profiling of chalcones as antioxidant and anti-inflammatory activities - Hafiz Aamir Ali Kharl; Muhammad Naeem; Shakira Ghazanfar; Arifa Mehreen; Hasnain Haider; Sumel Ashique; Sabina Yasmin; Fatimah M. Al-Salem; Md Yousuf Ansari (Inflammopharmacology, 2026)

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Synthesis of biocompatible novel multi-tailed indole-based resorcinarene for effective delivery of quercetin against multidrug-resistant S. aureus - Khadija Rehman; Tasmina Kanwal; Muhammad Hasnain; Rukesh Maharjan; Wajeeha Muzafar; Komal Rao; Salim Saifullah; Shabana Usman Simjee; Muhammad Raza Shah (Archives of Microbiology, 2026)

Wastewater based microbial fuel cells (MFCs) for electric power harnessing: A review - L. Syam Sundar; Syed M. Hasnain; Muhammad Waqar Ashraf (Next Research, 2026)

Geochemical modeling, evaluation of contaminants and impacts of land use, land cover patterns on groundwater quality in Khushab, Pakistan - Hasnain Abbas; Javed Iqbal; Syed Madhi Haider Kazmi; Maqsood Ahmed; Muhammad Ismail; Wajid Hussain (Journal of Contaminant Hydrology, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Experimental Evaluation of Pullout Resistance in Geosynthetic and Metallic Reinforcements - Muhammad Hanzalah Hasnain; Muhammad Zubair Asghar; Tauseef Anjum; Muhammad Waleed (Geotechnical and Geological Engineering, 2026)

Recombination hotspots and genetic variability in foot-and-mouth disease virus genomes: a comparative genomic and phylogeographic analysis - Shahid Hussain; Zixiao Jiang; Hasnain Israr; Jadoon Khan; Muhammad Nasir Riaz; Ijaz Ali; Chengjun Wu; Pir Tariq Shah (Archives of Virology, 2026)

Circular RNAs MTO1 and ZNF292 as potential diagnostic biomarkers in HIV patients treated with antiretroviral therapy - Mahnoor Fatima; Muhammad Shahid; Iram Amin; Hasnain Javed (Molecular Biology Reports, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Interfacial defect mitigation in HJT bottom cells for improved efficiency of monolithic perovskite/Si tandem solar cells - Mengmeng Chu; Hasnain Yousuf; Shanshan Gao; Maha Nur Aida; Xiaobo Wang; Muhammad Quddamah Khokhar; Junsin Yi (Chemical Engineering Journal, 2025)

Paleoenvironmental conditions and key drivers of organic matter accumulation in the early cretaceous Talhar Shale, Lower Indus Basin, Pakistan - Rizwan Sarwar Awan; Bo Liu; Qamar Yasin; David A. Wood; Hamad ur Rahim; Muhammad Amar Gul; Sajjad Ali; Khawaja Hasnain Iltaf; Ashar Khan (Journal of Asian Earth Sciences, 2025)

Silicic acid seed pre-treatment modulates growth and antioxidant responses in maize under drought stress - Abid Ali; Sara Zafar; Kashf Mehmood; Zuhair Hasnain; Muhammad Nawaz; Syed Muhammad Junaid Jalal Gilani; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (The Science of Nature, 2025)

The generative adversarial neural network with multi-layers stack ensemble hybrid model for landslide prediction in case of training sample imbalance - Wajid Hussain; Hong Shu; Hasnain Abbas; Sajid Hussain; Isma Kulsoom; Saqib Hussain; Hajra Mustafa; Aftab Ahmed Khan; Muhammad Ismail; Javed Iqbal (Stochastic Environmental Research and Risk Assessment, 2025)

Sulphur Nutrition Improves Plant Growth Performance Against a Specialist Herbivore by Eliciting Phenolic Defense and Nutrient Induction in Rapeseed - Muhammad Wajid Javed; Dilbar Hussain; Muhammad Hasnain; Mubshar Hussain; Imran Ali (Journal of Plant Growth Regulation, 2025)

Predicting ambient PM2.5 levels in the Yangtze River Delta with random forest algorithms: A machine learning approach - Ahmad Hasnain; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Basit Nadeem; Geng Wei; Waqas Akram Cheema; Muhammad Asif (Environment, Development and Sustainability, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

Sustainable water desalination with anti-wetting Janus membranes under simulated industrial low-grade fluctuated heat conditions in DCMD - Muhammad Mujahid; Muhammad Ali Hasnain; Ghafoor Ahmad; Chao Wang; Fan Xiao; Zhe Wu; Long-Fei Ren; Jiahui Shao (Process Safety and Environmental Protection, 2025)

Unpacking organizational capabilities and green Innovation for sustainable Performance: The role of environmental regulations in manufacturing industry - Hasnain Javed; Jianguo Du; Muhammad Farooq Islam (Journal of Cleaner Production, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Response surface optimization for biodiesel production from chicken fat via transesterification process over CaO-CeO2 catalyst - Hifza Rouf; Rehana Kousar; Zia Ul Haq; Syed Muhammad Wajahat ul Hasnain; Sajjad Haider; Salahuddin Khan; Sadaf Ul Hassan (Sustainable Chemistry and Pharmacy, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Prediction of nitrate concentration and the impact of land use types on groundwater in the Nansi Lake Basin - Javed Iqbal; Chunli Su; Hasnain Abbas; Jiaqi Jiang; Zhantao Han; Muhammad Yousuf Jat Baloch; Xianjun Xie (Journal of Hazardous Materials, 2025)

Insights into the strength development in cement-treated soils: An explainable AI-based approach for optimized mix design - Muhammad Hasnain Ayub Khan; Adel Abdallah; Olivier Cuisinier (Computers and Geotechnics, 2025)

Assessing the Influence of Potassium Fertilizer Variations on Growth, Yield, and Crop Quality of Sugarcane (Saccharum officinarum L.) Genotypes - Wajid Ali Hisbani; Bonface O. Manono; Muhammad Nawaz; Kashf Mehmood; Zuhair Hasnain; Afroz Rais; Sohail Irshad; Danish Ibrar; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (International Journal of Plant Production, 2025)

Predictive modeling of emulsion stability and drop characteristics using machine learning: A study on surfactant influence and time dynamics - Hasnain Ahmad Saddiqi; Asmat Ullah; Zainab Javed; Qazi Muhammad Ali; Muhammad Bilal Jan; Iftikhar Ahmad; Farooq Ahmad (Food and Bioproducts Processing, 2025)

A comprehensive review on ethno-pharmacological and phytochemical properties of selected species of genus Ophioglossum - Abdul Manan Yousaf; Sehrish Imran; Yamin Bibi; Muhammad Hasnain; Muhammad Imran Yousaf; Abdul Qayyum (South African Journal of Botany, 2024)

Biochar Outperforms Biochar-Compost Mix in Stimulating Ecophysiological Responses and Enhancing Soil Fertility under Drought Conditions - Zainul Abideen; Hans Werner Koyro; Maria Hasnain; Muhammad Iftikhar Hussain; Ali El-Keblawy; Mohamed A. El-Sheikh; Mirza Hasanuzzaman (Journal of Soil Science and Plant Nutrition, 2024)

Application of zinc nanoparticles as seed priming agent improves growth and yield of wheat seedlings grown under salinity stress by enhanced antioxidants activities and gas exchange attributes - Sara Zafar; Shahbaz Khan; Danish Ibrar; Muhammad Kamran Khan; Zuhair Hasnain; Kashf Mehmood; Afroz Rais; Safia Gul; Sohail Irshad; Muhammad Nawaz (Cereal Research Communications, 2024)

Molecular Characterization and Phylogenetic Analysis of Fasciola gigantica Based on ITS-1 Genetic Marker and copro-epidemiological Survey from Ruminants of Pakistan - Naunain Mehmood; Shafiah Zulfiqar; Hira Muqaddas; Muhammad Hasnain; Yadong Zheng; Habtye Bisetegn; Fahad Ahmed; Zafar Iqbal Khan; Furhan Iqbal (Acta Parasitologica, 2024)

Laboratory-based assessment of geotechnical characteristics of organic waste-amended soil for landfill biocover - Suaidah Rahim; Mohamed Hasnain Isa; Shahriar Shams; Muneerah Jeludin; Ena Kartina Abdul Rahman; Rozeana Hj Md Juani; Muhammad Raza Ul Mustafa; Teh Sabariah Abd Manan; Ahmad Hussaini Jagaba (Environmental Science and Pollution Research, 2024)

An electrochemical sensing potential of cobalt oxide nanoparticles towards citric acid integrated with computational approach in food and biological media - Huma Ajab; Ali Turab Jafry; Hasnain Sajid; Matthew A. Addicoat; Khurshid Ayub; Muhammad Zia Ul Haq (Food Chemistry, 2024)

Modelling and predicting lift force and trans-membrane pressure using linear, KNN, ANN and response surface models during the separation of oil drops from produced water - Hasnain Ahmad Saddiqi; Zainab Javed; Qazi Muhammad Ali; Asmat Ullah; Iftikhar Ahmad (Journal of Water Process Engineering, 2024)

Correction: Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Spatial distribution and health risks assessment of heavy metals in e-waste dumping sites from Pakistan - Muhammad Zaffar Hashmi; Sohaib Khan; Yasar N. Kavil; Saeed Saad Alelyani; Abdullah G. Al Sehemi; Ahmad Hasnain; Sidra Shakil; Shuhong Wang; Zulkifl Ahmed (Environmental Geochemistry and Health, 2024)

Artificial intelligence-based prediction models of bio-treated sand strength for sustainable and green infrastructure applications - Muhammad Naqeeb Nawaz; Ahmed Yar Akhtar; Waqas Hassan; Muhammad Hasnain Ayub Khan; Muhammad Muneeb Nawaz (Transportation Geotechnics, 2024)

Predicting ambient PM2.5 concentrations via time series models in Anhui Province, China - Ahmad Hasnain; Muhammad Zaffar Hashmi; Sohaib Khan; Uzair Aslam Bhatti; Xiangqiang Min; Yin Yue; Yufeng He; Geng Wei (Environmental Monitoring and Assessment, 2024)

Nanoscale zero-valent iron (NZVI) intercalated MXene (Ti3C2Tx) for removal of polycyclic aromatic hydrocarbons in wastewater - Muhammad Raza Ul Mustafa; Hifsa Khurshid; Mohamed Hasnain Isa (Journal of Environmental Chemical Engineering, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

The impact of mineral resource abundance on environmental degradation in ten mineral- rich countries: Do the green innovation and financial technology matter? - Hasnain Javed; Jianguo Du; Shuja Iqbal; Abdelmohsen A. Nassani; Muhammad Farhan Basheer (Resources Policy, 2024)

Identification and validation of restricted seed color polymorphic sites in Barley (Hordeum vulgare L.) using SNPs derived CAPS markers - Murad Ali; Danish Ibrar; Zuhair Hasnain; Afroz Rais; Shahbaz Khan; Kashf Mehmood; Sami Ullah; Ali Bakhsh; Safia Gul; Muhammad Musawir Khan; Waqar Khan; Muhammad Nisar; et al. (Genetic Resources and Crop Evolution, 2024)

Advancements in Ni and Co-based catalysts for sustainable syngas production via Bi-reforming of methane: A review of recent advances - Syed Muhammad Wajahat ul Hasnain; Ahmad Salam Farooqi; Bamidele Victor Ayodele; Abid Salam Farooqi; Khairuddin Sanaullah; Bawadi Abdullah (Journal of Cleaner Production, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Geochemical Characterization of Organic Rich Black Rocks of the Niutitang Formation to Reconstruct the Paleoenvironmental Settings during Early Cambrian Period from Xiangxi Area, Western Hunan, China - Rizwan Sarwar Awan; Chenglin Liu; Ashar Khan; Khawaja Hasnain Iltaf; Qibiao Zang; Yuping Wu; Sajjad Ali; Muhammad Amar Gul (Journal of Earth Science, 2023)

Revolutionizing Chronic Obstructive Pulmonary Disease Care with the Open AI Application: ChatGPT - Muhammad Hasnain; Asad Hayat; Akbar Hussain (Annals of Biomedical Engineering, 2023)

ChatGPT Applications and Challenges in Controlling Monkey Pox in Pakistan - Muhammad Hasnain (Annals of Biomedical Engineering, 2023)

A critical analysis of wastewater use in agriculture and associated health risks in Pakistan - Natasha; Muhammad Shahid; Sana Khalid; Behzad Murtaza; Hasnain Anwar; Ali Haidar Shah; Aneeza Sardar; Zunaira Shabbir; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

Engineering of oxygen vacancy defect in CeO2 through Mn doping for toluene catalytic oxidation at low temperature - Ahmed Ismail; Muhammad Zahid; Sharafat Ali; Syed ul Hasnain Bakhtiar; Nauman Ali; Adnan Khan; Yujun Zhu (Environmental Research, 2023)

Potential Breeding Strategies for Improving Salt Tolerance in Crop Plants - Muhammad Afzal; Salah El Sayed Hindawi; Salem Safer Alghamdi; Hussein H. Migdadi; Muhammad Altaf Khan; Muhammad Usama Hasnain; Muhammad Arslan; Muhammad Habib ur Rahman; Muhammad Sohaib (Journal of Plant Growth Regulation, 2023)
Salinity is one of the significant abiotic stresses that negatively affect plant production processes, growth, and development, which ultimately reduce yield. Plants adapt specific mechanisms to withstand saline conditions and activate diverse salt tolerance genes to counter osmotic and oxidative stresses induced by salinity. Genetic development in salinity tolerance is quite complex, while advancement has made less progress than expectation over the past few decades. Generating an explosion of genetics- and genomics-related information and technology in recent decades pledge to deliver innovative and advanced resources for the potential production of tolerant genotypes. Despite considerable progress in defining the primary salinity tolerance mechanisms, main obstacles are yet to be solved in the translation and incorporation of the resulting molecular knowledge into the plant breeding activities. Diverse approaches are proposed to enhance plant breeding efficacy to increase plant productivity in saline environments. Understanding the genetics of salt tolerance is a difficult task because multiple genes and pathways are involved. Important advances in tools and methods for updating and manipulating plant genomics knowledge provide detailed insights and dissect the salinity tolerance mechanism accomplished by the breeding goals. Genome-wide analyses (GWA) identify SNP variations and functional effects that appear to be the way of the future for developing salinity-tolerant plants. Gene discovery to manipulate the molecular mechanisms which underlie the complex phenotype of salinity tolerance methods, identification of genes, QTL, association mapping, linkage, and functional genomics, such as transcript identifying and proteins related to salinity, is necessary. The present analysis also discussed some of the opportunities and challenges, focusing on molecular breeding strategies used in conjunction with other crop development approaches to growing elite salt-tolerant lines.

Formation and propagation of dust cloud induced by Ultar rock avalanche on April 9, 2018, in Karimabad, Hunza, Pakistan - Hasnain Gardezi; Aiguo Xing; Muhammad Bilal; Yu Zhuang; Shahmir Janjua (Landslides, 2023)

Efficient detoxification of textile wastewater by applying Chenopodium album nanoparticles and its application in simulated metal-bearing effluents removal - Neelma Munir; Rabia Tariq; Zainul Abideen; Maria Hasnain; Muhammad Iftikhar Hussain; Rukhama Haq (Environmental Science and Pollution Research, 2023)

A novel approach for power enhancement of vertical mounted bifacial photovoltaic system using reflecting mirrors - Muhammad Aleem Zahid; Hasnain Yousuf; Youngkuk Kim; Junsin Yi; Suresh Kumar Dhungel (Journal of Cleaner Production, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Groundwater fluoride and nitrate contamination and associated human health risk assessment in South Punjab, Pakistan - Javed Iqbal; Chunli Su; Mengzhu Wang; Hasnain Abbas; Muhammad Yousuf Jat Baloch; Junaid Ghani; Zahid Ullah; Md. Enamul Huq (Environmental Science and Pollution Research, 2023)

Assessing the ambient air quality patterns associated to the COVID-19 outbreak in the Yangtze River Delta: A random forest approach - Ahmad Hasnain; Yehua Sheng; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Zulkifl Ahmed; Yong Zha (Chemosphere, 2023)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

A study of reservoir potential of Cretaceous–Paleocene successions of Nizampur basin, Khyber Pakhtunkhwa, Pakistan: constraints from fracture analysis, petrography and geochemistry - Muhammad Naveed Anjum; Abbas Ali Naseem; Muhammad Yaseen; Ali Hasnain; Junaid Khan; Jawad Ahmad (Carbonates and Evaporites, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Effect of slow release nitrogenous fertilizers and biochar on growth, physiology, yield, and nitrogen use efficiency of sunflower under arid climate - Muhammad Waqar; Muhammad Habib-ur-Rahman; Muhammad Usama Hasnain; Shahid Iqbal; Abdul Ghaffar; Rashid Iqbal; Muhammad Iftikhar Hussain; Ayman EL Sabagh (Environmental Science and Pollution Research, 2022)
Sunflower plants need nitrogen consistently and in higher amount for optimum growth and development. However, nitrogen use efficiency (NUE) of sunflower crop is low due to various nitrogen (N) losses. Therefore, it is necessary to evaluate the advanced strategies to minimize N losses and also improve sunflower productivity under arid climatic conditions. A field trial was conducted with four slow release nitrogenous fertilizers [SRNF (bacterial, neem, and sulfur-coated urea and N loaded biochar)] and three N levels (100% = 148 kg N ha −1 , 80% = 118 kg N ha −1 , and 60% = 89 kg N ha −1 ) of recommended application (100%) for sunflower crop under arid climatic conditions. Results showed that neem-coated urea at 148 kg N ha −1 significantly enhanced crop growth rate (CGR) (19.16 g m −2 d −1 ) at 60–75 days after sowing (DAS); leaf area index (2.12, 3.62, 5.97, and 3.00) at 45, 60, 75, and 90 DAS; and total dry matter (14.27, 26.29, 122.67, 410, and 604.33 g m −2 ) at 30, 45, 60, 75, and 90 DAS. Furthermore, higher values of net leaf photosynthetic rate (25.2 µmol m −2 s −1 ), transpiration rate (3.66 mmol s −1 ), and leaf stomatal conductance (0.39 mol m −2 s −1 ) were recorded for the same treatment. Similarly, neem-coated urea produced maximum achene yield (2322 kg ha −1 ), biological yield (9000 kg ha −1 ), and harvest index (25.8%) of the sunflower crop. Among various N fertilizers, neem-coated urea showed maximum NUE (20.20 kg achene yield kg −1 N applied) in comparison to other slow release N fertilizers. Similarly, nitrogen increment N 60 showed maximum NUE (22.40 kg grain yield kg −1 N applied) in comparison to N 80 and N 100 . In conclusion, neem-coated urea with 100% and 80% of recommended N would be recommended for farmers to get better sunflower productivity with sustainable production and to reduce the environmental nitrogen losses.

RETRACTED ARTICLE: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Preliminary investigation and dynamic analysis of a multiphase ice-rock avalanche on July 5, 2021, in the upper Naltar valley, Gilgit, Pakistan - Hasnain Gardezi; Aiguo Xing; Muhammad Bilal; Yu Zhuang; Shoaib Muhammad; Shahmir Janjua (Landslides, 2022)

Multidimensional perspective of green financial innovation between green intellectual capital on sustainable business: the case of Pakistan - Hafeez Ullah; Zhuquan Wang; Muhammad Mohsin; Weiying Jiang; Hasnain Abbas (Environmental Science and Pollution Research, 2022)

Mitochondrial phylogenetic and diversity analysis in Azi-Kheli buffalo - Farhad Ali; Ijaz Ahmad; Muhammad Ijaz Ali; Muhammad Hasnain Riaz; Nadar Khan; Obaid Ullah; Faizul Hassan; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tahir Khan; Irshad Ahmad; Muhammad Tariq Zeb (Tropical Animal Health and Production, 2021)

Switching behaviors toward green brands: evidence from emerging economy - Syed Hasnain Alam Kazmi; Muhammad Saeed Shahbaz; Muhammad Shujaat Mubarik; Junaid Ahmed (Environment, Development and Sustainability, 2021)

Spatio-temporal trends and climatology of atmospheric chlorinated hydrocarbons over Pakistan - Ahmad Hasnain; Yong Zha; Muhammad Zaffar Hashmi; Fatima Rahim; Yufeng He; Yehua Sheng (Arabian Journal of Geosciences, 2021)

Effect of co-application of wastewater and freshwater on the physiological properties and trace element content in Raphanus sativus: soil contamination and human health - Natasha; Muhammad Shahid; Aneeza Sardar; Hasnain Anwar; Sana Khalid; Sajid Hussain Shah; Ali Haidar Shah; Muhammad Bilal (Environmental Geochemistry and Health, 2021)

A comparative analysis of attabad landslide on january 4, 2010, using two numerical models - Hasnain Gardezi; Muhammad Bilal; Qiangong Cheng; Aiguo Xing; Yu Zhuang; Tahir Masood (Natural Hazards, 2021)

Risk assessment of heavy metal(loid)s via Spinacia oleracea ingestion after sewage water irrigation practices in Vehari District - Aneeza Sardar; Muhammad Shahid; Natasha; Sana Khalid; Hasnain Anwar; Muhammad Tahir; Ghulam Mustafa Shah; Muhammad Mubeen (Environmental Science and Pollution Research, 2020)

Transcription Factor TaDof1 Improves Nitrogen and Carbon Assimilation Under Low-Nitrogen Conditions in Wheat - Ammarah Hasnain; Muhammad Irfan; Aftab Bashir; Asma Maqbool; Kauser A. Malik (Plant Molecular Biology Reporter, 2020)

Attenuating the adverse aspects of water stress on wheat genotypes by foliar spray of melatonin and indole-3-acetic acid - Sara Zafar; Muhammad Akhtar; Shagufta Perveen; Zuhair Hasnain; Aansa Khalil (Physiology and Molecular Biology of Plants, 2020)

Effects of selected synthetic insecticides on the total and differential populations of circulating haemocytes in adults of the red cotton stainer bug Dysdercus koenigii (Fabricius) (Hemiptera: Pyrrhocoridae) - Zahid Mahmood Sarwar; Mamuna Ijaz; Muhammad Altaf Sabri; Hasnain Yousaf; Muhammad Mohsan (Environmental Science and Pollution Research, 2018)

Artificial Neural Network (ANN) for Modelling Adsorption of Lead (Pb (II)) from Aqueous Solution - Taimur Khan; Muhammad Raza Ul Mustafa; Mohamed Hasnain Isa; Teh Sabariah Binti Abd Manan; Yeek-Chia Ho; Jun-Wei Lim; Nur Zulaikha Yusof (Water, Air, & Soil Pollution, 2017)

Prediction of pore-water pressure response to rainfall using support vector regression - Nuraddeen Muhammad Babangida; Muhammad Raza Ul Mustafa; Khamaruzaman Wan Yusuf; Mohamed Hasnain Isa (Hydrogeology Journal, 2016)

Biochar enhances the cadmium tolerance in spinach (Spinacia oleracea) through modification of Cd uptake and physiological and biochemical attributes - Uzma Younis; Saeed Ahmad Malik; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Hasnain Raza Shah; Rabia Abdur Rehman; Niaz Ahmad (Environmental Science and Pollution Research, 2016)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

Synthesis and biological evaluation of new [1,3,4]thiadiazepino[7,6-b]quinolin-2-amines as potent anti-microbial agents - Hasnain Muhammad Raza; Nada-E-Ali Rizvi; Hamid Latif Siddiqui; Arshad Javaid; Mazhar Iqbal (Medicinal Chemistry Research, 2013)

Bacterial Cr(VI) Reduction Concurrently Improves Sunflower (Helianthus Annuus L.) Growth - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2005)

Chromate resistantBacillus cereus augments sunflower growth by reducing toxicity of Cr (VI) - Muhammad Faisal; Shahida Hasnain (Journal of Plant Biology, 2005)

Comparative study of Cr(VI) uptake and reduction in industrial effluent by Ochrobactrum intermedium and Brevibacterium sp. - Muhammad Faisal; Shahida Hasnain (Biotechnology Letters, 2004)

Inoculating wheat seedlings with exopolysaccharide-producing bacteria restricts sodium uptake and stimulates plant growth under salt stress - Muhammad Ashraf; Shahida Hasnain; Odile Berge; Tariq Mahmood (Biology and Fertility of Soils, 2004)